Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s13256-015-0541-8
|View full text |Cite
|
Sign up to set email alerts
|

Remote cerebellar hemorrhage following thoracic spinal surgery of an intradural extramedullary tumor: a case report

Abstract: IntroductionRemote cerebellar hemorrhage is a rare complication of spinal surgery. Although loss of cerebrospinal fluid seems to play an important role in the pathogenesis of this complication, the detailed mechanism of remote cerebellar hemorrhage after spinal surgery remains unclear. We report the case of a patient with remote cerebellar hemorrhage following thoracic spinal surgery of an intradural extramedullary tumor and discuss this entity with reference to the literature.Case presentationA 57-year-old Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Clinical suspicion and early detection are critical. When patients present with neurological signs or symptoms suggestive of raised intracranial pressure following spine or supratentorial surgery, the drains should be checked for increased volumes of drained fluid (and possibly suction stopped) [21], [22]. Prompt evaluation with neuroimaging should be performed [1], [21].…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Clinical suspicion and early detection are critical. When patients present with neurological signs or symptoms suggestive of raised intracranial pressure following spine or supratentorial surgery, the drains should be checked for increased volumes of drained fluid (and possibly suction stopped) [21], [22]. Prompt evaluation with neuroimaging should be performed [1], [21].…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…So closed wound suction drainage is recommended for spinal surgery especially tumor resection, and the time to stop drainage is determined by the complaints of patients including headache and emesis [8]. In other words, early diagnosis is also very important for the treatment of intracranial hemorrhage after spinal surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Patients rarely manifested with visual impairment, neck rigidity, or irritability. These symptoms encountered in the early phase after spinal surgery can indicate a potential intracranial hemorrhage, and timely radiological examination is warranted ( 12 , 13 ). CT is generally the first-line imaging modality for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that intracranial venous or arterial hemorrhage may be caused by low intracranial pressure secondary to excessive intraoperative or postoperative leakage of cerebrospinal fluid ( 12 ). When the intracranial pressure decreases, the cerebella shift may lead to the traction or occlusion of superior cerebellar veins, resulting in subsequent hemorrhagic venous infarction ( 13 ). Pallud et al also pointed out that cerebellar hemorrhage may be secondary to cerebellar occlusion and edema caused by traction and tear of the superior cerebellar veins ( 15 ).…”
Section: Discussionmentioning
confidence: 99%